THE RELATIONSHIP BETWEEN LEARNING INDEPENDENCE AND UTILIZATION OF LEARNING SOURCES WITH MATHEMATICAL LEARNING OUTCOMES OF STUDENTS SMP MUHAMMADIYAH 1 YOGYAKARTA - Riska Tri Pratiwi; Harina Fitriyani (Universitas Ahmad Dahlan, 2017)
This research is motivated by the lack of learning independence and the use of learning resources that occur thus might affect the level of student learning outcomes. The purpose of this study was to determine the presence or absence of positive and significant relationships between learning independence and the use of learning resources with studentsâ€™ mathematics learning outcomes in class VIII of even semester in SMP Muhammadiyah 1 Yogyakarta Academic of 2015/2016. The population in this study was all VIII class students as much 7 classes by total students 212. The sample was taken with a random sampling technique and derived class VIII B as a class sample with 27 students. Data collection technique used to test techniques to determine the result of mathematics learning outcomes and questioner techniques to determine the learning independence and use of learning resources. Instrument testing used validity and reliability testing. The technic to analysis test which is a test of homogeneity, normality, independent, and linearity test. Analysis of the data for testing hypotheses used correlation analysis and linear regression analysis. The results showed that F_count= 5,608648681 and F_table= 3,40 so F_countâ‰¥F_table which means there is a positive and significant relationship between learning independence and use of learning resources that occur thus might affect the level of student learning outcomes, with a coefficient of determination (r) = 0,5643728384 and Å· = -23,63 + 0,49x1+ 0,76x2. The value of Relatively contribution of X1 = 32,645%, X2= 67,355% and value of effectively contribution of X1 = 10,398%, X2= 21,454%.